2012
DOI: 10.1590/s0004-28032012000400007
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for survival in patients with colorectal liver metastases: experience of a single brazilian cancer center

Abstract: -Context -Liver metastases are a common event in the clinical outcome of patients with colorectal cancer and account for 2/3 of deaths from this disease. There is considerable controversy among the data in the literature regarding the results of surgical treatment and prognostic factors of survival, and no analysis have been done in a large cohort of patients in Brazil. Objectives -To characterize the results of surgical treatment of patients with colorectal liver metastases, and to establish prognostic factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 21 publications
(27 reference statements)
0
12
0
9
Order By: Relevance
“…All identified studies were observational design studies involving a total of 10621 patients. Seven studies were from USA [5, 7, 9, 16, 21, 22, 24], four from Italy [4, 8, 12, 13], three from Japan [3, 14, 18], two from UK [11, 25], two from Germany [20, 23], one from Sweden [2], one from France [6], one from Spain [10], one from Brazil [15], one from China [17], one from Canada [19], and one from the Netherlands [26]. The blood product transfusion rate was highly variable across studies ranging from 13.5% to 91.5%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All identified studies were observational design studies involving a total of 10621 patients. Seven studies were from USA [5, 7, 9, 16, 21, 22, 24], four from Italy [4, 8, 12, 13], three from Japan [3, 14, 18], two from UK [11, 25], two from Germany [20, 23], one from Sweden [2], one from France [6], one from Spain [10], one from Brazil [15], one from China [17], one from Canada [19], and one from the Netherlands [26]. The blood product transfusion rate was highly variable across studies ranging from 13.5% to 91.5%.…”
Section: Resultsmentioning
confidence: 99%
“…The impact of PBT on OS and disease-free survival (DFS) was evaluated in 21 [29, 11, 12, 1519, 2126] and 11 [6, 8, 11, 12, 1517, 19, 20, 22] studies, respectively. The 5-year OS and DFS of transfused patients ranged from 21.5% to 62.7% and 14.7% to 42% respectively vs .…”
Section: Resultsmentioning
confidence: 99%
“…Survival rates 5 and 10 years after diagnosis are approximately 59% and 20%, respectively in American center, 4,5 though no studies have assessed survival rates in South American populations. Our previous work assesses short‐term survival in a South American colorectal cancer population and found a 5‐year overall survival of 64.9%, 6 though long‐term survival has not yet been investigated. Therefore, a comprehensive study of the factors associated with long‐term survival in South American populations is needed to improve surgical selection approaches and decrease morbidity and futile locoregional treatments 7 …”
Section: Introductionmentioning
confidence: 99%
“…Tumor size, positive surgical margins, lymphnode involvement, lymphovascular invasion, carcinoembrionic antigen (CEA) level, poor histological differentiation and tumor budding were considered the most important prognostic factors both in colorectal cancer and in metastatic colorectal cancer (mCRC) [6] . Studies have shown that both higher prediagnosis plasma levels of vitamin D and regular aspirin use are associated with improved outcomes in patients with advanced colorectal disease [7] . A high body mass index (BMI) and alack of physical exercise are also associated with both the development of colorectal cancer and poorer outcomes [8] .…”
Section: Introductionmentioning
confidence: 99%